2019
DOI: 10.1007/s13213-019-01470-x
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt stress response in soybean plants with the endophytic bacterial isolate Curtobacterium sp. SAK1

Abstract: Background Salinity has been a major abiotic stressor that reduce the productivity. Previous studies reported that endophytic bacteria produce plant stress response hormones, antioxidants, and enzymes such as ACC deaminase. Augmentation of these metabolites and enzymes by endophytes mitigates the stress effects of salinity and improves plant growth and productivity. Methods Bacterial endophytes were isolated from Artemisia princeps Pamp, and evaluated for indole-3-acetic acid (IAA), abscisic acid (ABA), sidero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 66 publications
3
56
0
Order By: Relevance
“…Modulation of phytohormones and accumulation of nutrients against the hyperosmotic and hypo-nutritive conditions is an important role of HT-PGPR to confer symbiotic association and promote growth and productivity of plants. Studies confirmed that under salt stress, expression of genes for auxin like compounds increase in HT-PGPR and compensate plant’s requirement of growth hormone [102] , [89] . Apart from the improvement in growth, there is also evidence that phytohormones produced by HT-PGPR showed role in the exclusion of ionic salts.…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 75%
See 1 more Smart Citation
“…Modulation of phytohormones and accumulation of nutrients against the hyperosmotic and hypo-nutritive conditions is an important role of HT-PGPR to confer symbiotic association and promote growth and productivity of plants. Studies confirmed that under salt stress, expression of genes for auxin like compounds increase in HT-PGPR and compensate plant’s requirement of growth hormone [102] , [89] . Apart from the improvement in growth, there is also evidence that phytohormones produced by HT-PGPR showed role in the exclusion of ionic salts.…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 75%
“…HT-PGPR employ a vast array of mechanisms including production of low molecular weight organic acids, chelating agents and ion exchange for solubilization of P, Zn and potassium (K) in saline soil [87] , [88] . Minimizing the rhizospheric competition in nutrient scant stressed soils, some microbes through penetration or nodulation establish themselves as endophytes and in turn benefit the plant by assimilating nutrients and increasing survival/ adaption rate [89] . P is an important macronutrient required in large quantities by the plant i.e.…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 99%
“…Cobrançosa cultivar had also several associated isolates described as potential antagonists of phytopathogens, such as Bacillus megaterium [80], Bacillus subtilis [81], Pantoea vagans [82] and Pseudomonas graminis [83]. Other isolates associated to Cobrançosa cultivar have been described to protect plants on stressful environments (Curtobacterium oceanosedimentum [84]). In contrast, microorganisms described as plant pathogens were detected on cv.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes improve plant growth by secreting phytohormones and consequently help in nutrition improvement using bidirectional nutrient transfer and enhancement of the health of plants by protecting them against phytopathogens (Andreozzi et al, 2019;Shen et al, 2019). Plant-endophyte interaction triggers the protection of plants against harmful conditions of the environment such as heavy metal presence and drought (Khan et al, 2019;Kushwaha et al, 2019). Endophytes are numerous and studies have it that they are present in many plants; they became important due to their capacity to produce many bioactive metabolites and biotechnologically relevant enzymes (Khan et al, 2014;Rajamanikyam et al, 2017).…”
Section: Introductionmentioning
confidence: 99%